USING MODERN METHODS IN TEACHING PHYSICS: ELEMENTS OF ROBOTICS AS TEACHING TOOLS - Sardorjon Nabiyev; Ixtiyor Tursunov (Web of Journals Publishing, 2023)
In this article, the possibilities of using robotics elements in the teaching of physics, the use of robotics elements as a means of developing and educating students, serving to fully master the educational materials, to strengthen knowledge in science, and to form practical skills and competencies information is provided. Also, the levels of teaching robotics educational materials to school students are highlighted.
Keywords: modern pedagogical technologies, robotics, integration, tool, motivation, technical knowledge.